GMAT Math : Simplification rule

Let’s use a GMAT data sufficiency example to elaborate the point

What is the value of y, if y(x-1) = 3(x-1)(x-2)?

  1. x = 1
  2. x = 3

Readers are encouraged to take time to solve the above problem πŸ™‚

….

….

….

….

Solution:

It is tempting to simplify the equation to :

y = 3(x – 2)

For x = 1 and x = 2 we have values of y = -3 and 1 respectively

Herein lies a pitfall – simplifying equations assumes that we are never dividing by 0 : this is a cardinal rule which must be followed at all times

For x = 1,

y (0) = 3 (0) (-2)

y = 3 (0) (-2) / (0) = undefined! J

So statement (1) does not help us get to the value of y

Statement (2) on the other hand works just fine

y (2) = 3 (2) (1)

y = 3

Hence, we go with option (B)

Remember this important pitfall of simplification – The GMAT Quant section has been known to test it when you are closing in towards Q50/51 πŸ™‚